Uniform distribution of graphene oxide sheets into a poly-vinylidene fluoride nanoparticle matrix through shear-driven aggregation. Issue 27 (23rd June 2016) - Sheng, Xinxin; Xie, Delong; Zhang, Xinya; Zhong, Li; Wu, Hua; Morbidelli, Massimo
Abstract : Shear-driven aggregation of binary (A + B) colloidal dispersions can realize nanocomposites with B the continuous phase and A uniformly distributed in B. Abstract : A general methodology has been developed for preparing nanocomposites with uniform, random distribution of fillers in polymer matrices, purely based on intense shear-driven aggregation, while avoiding filler aggregation. This procedure is demonstrated for a binary colloid composed of graphene oxide (GO) sheets and poly-vinylidene fluoride (PVDF) nanoparticles (NPs), both negatively charged and stable at rest. On the other hand, the PVDF NPs are shear-active ( i.e. aggregation occurs under intensive shear), while the GO sheets are shear-inactive. It is found that when the two suspensions are mixed and the resulting binary colloid is forced to pass through a microchannel (MC) device (at a very high shear rate, G = 1.2 × 10 6 s −1 ), the shear-inactive GO sheets are captured and well distributed inside the PVDF NP clusters or gels. In addition, it is shown that in order to have 100% capture efficiency for the GO sheets, a minimum solid content of the binary colloid is required, which can be identified experimentally as the minimum leading to gelation after passing through the MC only one time.